FEMINIST MOVEMENTS IN INDIA: A Study of Stree Sangharsh, Forum Against Oppression of Women, Vimochana, and Saheli - Kumari, Tanima (Journal of Dharma, 2016)
The present paper is an attempt at feminist historiography that revisits the role of post 1970s women organizations, specifically focusing on Stree Sangharsh, Forum Against Oppression of Women, Vimochana, and Saheli. Indian women adopted the mechanism of 'gendered resistance' against the vilified society in various anti-patriarchal agitations, like antialcohol and anti-price rise movements, campaigns against sati, dowry, and rape, and campaigned to raise the consciousness of women towards their rights through protest march, legislative debate, street theatre and other interactive modes. Analyzing activist feminist movements juxtaposed with theorizations, the paper concludes with the Indian feminists' attempt to create feminist solidarity of bhaginivarg (sisterhood) as posited by Padma Anagol, which resounds bell hooks'idea of sisterhood.